Implementation and analysis of heart beat detector based on Arduino microcontroller: article - Mohd Dahri, Mohd Amini (2013)
This paper proposes to implement the heart beat detector and analyzer based on Arduino microcontroller. Heart beat rate or pulse rate can be influence by many things including age, weight, physical activity, stress, illness, injury and medications the person are taking. The objectives of this work are to design a simple and easy heartbeat detector using optical sensors compared to ECG electrode and can be analysed the heart rate. For this project, pulse sensor is used as the sensor to detect the heart beat by put on the fingertip, earlobe or any capillary tissue on the body part, and the heart beat is processed by Arduino Microcontroller. It displayed the heartbeat waveform by the Pulse Sensor Amped Visualizer using processing software then analyzed for overweight and body posture categories person. The function to analyse these categories is to make sure that this heartbeat detector can be used for medication. The picture of heart beat waveform from visualizer will be send to the webpage using Ethernet Shield for monitoring. This detector produced the heart rate data of waveform, interbeat interval and beat per minute on visualizer that can be analyze to see the difference condition of the various person category that can be monitored on the web using Ethernet shield. The function to monitor on web is to help both the doctor and patient for medication procedure which the patient that need regular check-up for heart beat does not need to go to hospital and just send their heartbeat data to the web for monitoring by the doctor. This method cannot been achieved by using the ECG electrode procedure since the ECG device only used on the hospital and conducted by expertise.